2002
DOI: 10.1081/dis-120015971
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Guest Partitioning Within Dendrimer–Surfactant Supramolecular Assemblies

Abstract: Electrostatic interactions are used to create a template-assisted supramolecular assembly consisting of a polymeric dendrimer at the core and amphiphilic substrates on the periphery. The dendrimer generation and the chemical structure of the amphiphiles are varied to construct multiple and distinct microenvironments within the dendrimer-ligand complex for encapsulation of small guest molecules. In particular, these investigations employ a guest molecule that is a neutral fluorescent probe that exhibits an emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The structure, nature, and interaction mechanism of the dendrimer−surfactant aggregates were reported by several groups. , The aggregates create a template-assisted supramolecular assembly consisting of a dendrimer at the core and amphiphilic surfactants on the surface by electrostatic interactions. , Surfactants can also penetrate the surface charge barriers of dendrimers and localize in their interior cavities by hydrophobic interactions or hydrogen - bonding interactions . Although solubilization of fluorescent dyes such as pyrene and prodan by the dendrimer−surfactant aggregations was carried out to investigate the guest partition within the supramolecular assemblies, , no study reported the applications of the aggregates as drug carriers. It was reported that both dendrimers and surfactants can help drugs to penetrate through skin barriers, which is the main challenge to transdermal drug delivery. The dendrimer−surfactant aggregates are expected to increase the drug loading efficiency, adhesive property, and penetration ability of dendrimers, modulate the drug release behaviors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure, nature, and interaction mechanism of the dendrimer−surfactant aggregates were reported by several groups. , The aggregates create a template-assisted supramolecular assembly consisting of a dendrimer at the core and amphiphilic surfactants on the surface by electrostatic interactions. , Surfactants can also penetrate the surface charge barriers of dendrimers and localize in their interior cavities by hydrophobic interactions or hydrogen - bonding interactions . Although solubilization of fluorescent dyes such as pyrene and prodan by the dendrimer−surfactant aggregations was carried out to investigate the guest partition within the supramolecular assemblies, , no study reported the applications of the aggregates as drug carriers. It was reported that both dendrimers and surfactants can help drugs to penetrate through skin barriers, which is the main challenge to transdermal drug delivery. The dendrimer−surfactant aggregates are expected to increase the drug loading efficiency, adhesive property, and penetration ability of dendrimers, modulate the drug release behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Surfactants can also penetrate the surface charge barriers of dendrimers and localize in their interior cavities by hydrophobic interactions or hydrogen-bonding interactions. 6 Although solubilization of fluorescent dyes such as pyrene and prodan by the dendrimersurfactant aggregations was carried out to investigate the guest partition within the supramolecular assemblies, 10,16 no study reported the applications of the aggregates as drug carriers. It was reported that both dendrimers and surfactants can help drugs to penetrate through skin barriers, which is the main challenge to transdermal drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al reported that aliphatic chainmodified hyperbranched poly(sulfone-amine) (HPSA) and poly(amido-amine) (HPAMAM) could trap water-soluble dyes into chloroform phase efficiently [46][47][48][49]. Besides this kind of molecule-level encapsulation, Edirisinghe et al [50][51][52][53] also reported some new methods to prepare different kinds of encapsulated microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…Deconvolution of the overall prodan fluorescence emission spectrum into a sum of overlapping Gaussian functions enables an interpretation of the location of prodan within discrete microdomains of different relative polarities. We have used prodan to characterize the noncovalent interactions that influence the partitioning of guest molecules within surfactant aggregates such as aqueous micelles, ,, reverse micelles, and unilamellar vesicles 45,47 and within supramolecular assemblies of polymeric dendrimers and surfactants . The polarity and water accessibility of the microregions of surfactant aggregates differ considerably and give rise to distinct emission λ max .…”
Section: Introductionmentioning
confidence: 99%
“…We have used prodan to characterize the noncovalent interactions that influence the partitioning of guest molecules within surfactant aggregates such as aqueous micelles, 42,44,45 reverse micelles, [43][44][45] and unilamellar vesicles 45,47 and within supramolecular assemblies of polymeric dendrimers and surfactants. 48 The polarity and water accessibility of the microregions of surfactant aggregates differ considerably and give rise to distinct emission λ max . The fluorescence signature of prodan in these surfactant aggregates suggests that several intermolecular forces influence probe distribution, including hydrophobic interactions, van der Waals (i.e., dipole-dipole) forces, and electrostatic association between the π electrons of the aromatic ring of prodan and cationic surfactant headgroups.…”
Section: Introductionmentioning
confidence: 99%